Aggressive atypical cystic fibromatosis of the pancreas: a case report and literature review - Yang, Xianhong; Xu, Zhenji; Liu, Yangyingqiu; Feng, Tao (Frontiers in Oncology, 2025)
Aggressive fibromatosis of the pancreas (AFP) is a rare, non-epithelial, aggressive, benign soft tissue tumor of the pancreas that is characterized by β-catenin-positive expression. Due to its rarity, it is often misdiagnosed as a malignant pancreatic tumor. In this report, we present a case of aggressive atypical cystic fibromatosis that is specifically localized to the pancreas. We emphasize the key imaging features essential for diagnosing and assessing the aggressiveness of this condition, along with its pathological characteristics, pathogenesis, and surgical treatment. Progressive delayed enhancement, marked restricted diffusion, and aggressive features can aid in differentiation, and nuclear β-catenin positivity is highly characteristic of this condition. A 22-year-old woman was admitted following the incidental discovery of a cystic-solid pancreatic mass during a routine medical examination. This patient underwent preoperative ultrasound, computed tomography, and magnetic resonance imaging. The identified lesion was subsequently surgically resected, and a histopathological examination confirmed the presence of AFP. Notably, the tumor was found incidentally, as the patient was asymptomatic. Radiologists should consider the possibility of aggressive fibromatosis in patients presenting with pancreatic tumors, as surgical resection can lead to a cure. Therefore, comprehensive imaging analysis is crucial for making an accurate preoperative diagnosis and providing appropriate treatment.